Asymptotic stability of fractional impulsive neutral stochastic partial integro-differential equations with infinite delay. Issue 1 (2nd January 2017) - Bahuguna, D.; Sakthivel, R.; Chadha, A.
ABSTRACT: In this article, we investigate the existence and asymptotic stability in p -th moment of a mild solution to a class of neutral stochastic integro-differential equation of fractional order involving non-instantaneous impulses with infinite delay in a Hilbert space. A new set of sufficient conditions proving existence and asymptotic stability of mild solution is derived by utilizing solution operator, functional analysis, stochastic analysis and fixed point technique. Finally, an example is provided to illustrate the obtained abstract result.